Multi-Disciplinary Discharge Coordination Team to Overcome Discharge Barriers and Address the Risk of Delayed Discharges - Ibrahim H; Harhara T; Athar S; Nair SC; Kamour AM (Dove Medical Press, 2022)
Halah Ibrahim,1,2 Thana Harhara,2 Syed Athar,2 Satish C Nair,3 Ahsraf M Kamour2 1Department of Medicine, Khalifa University College of Medicine and Health Sciences, Abu Dhabi, United Arab Emirates; 2Department of Medicine, Sheikh Khalifa Medical City, Abu Dhabi, United Arab Emirates; 3Department of Academic Affairs, Tawam Hospital, College of Medicine, UAE University, Al Ain, United Arab EmiratesCorrespondence: Satish C NairDepartment of Academic Affairs, Tawam Hospital, Post Box 15258, Al Ain, United Arab Emirates, Tel +97137074739, Email satchi2000@outlook.comBackground: Delays in hospital discharge occur when patients are medically cleared but continue to remain hospitalized. Discharge delays can result in reduced levels of treatment, placing patients at risk of functional decline, falls and hospital-related adverse events. The Institute of Medicine has highlighted timely, efficient, and safe hospital discharge as a marker for quality care. Hospitals, however, are often unable to meet discharge targets. Research has shown improvements in discharge planning through system-level approaches that integrate health care and social work. The purpose of this study is to describe the development and implementation of a multidisciplinary team intervention to overcome discharge barriers for patients with prolonged hospitalization. We also evaluated the impact of the intervention on length of stay, readmission rates and care team satisfaction and morale.Methods: A multidisciplinary discharge coordination team met weekly to proactively raise and resolve patient-related discharge issues for all patients admitted to the general medicine wards. Members included hospitalists, case managers, social workers, hospital finance representatives, and patient representatives. One of the hospital physicians facilitated the meetings.Results: Barriers to discharge included patient and family reluctance to discharge, medical delays in performing diagnostic tests or procedures, long-term care facility acceptance delays, and prolonged wait times for insurance approvals. Our multipronged approach decreased length of stay in our delayed discharge patient population from 15.45 days to 9.04 days, a 41.5% reduction, without an increase in readmissions. The healthcare team perceived the weekly multidisciplinary team meetings quite positively; 90% of respondents agreed that the meetings improved communication and increased their sense of support.Conclusion: Our intervention was successful in improving hospital processes to overcome barriers to patient discharge. We believe that similar multidisciplinary meetings can be implemented in hospitals throughout the region to decrease risks of prolonged hospitalization and, ultimately, improve hospital efficiency and care delivery.Keywords: discharge planning, discharge delays, length of stay, prolonged hospitalization, multidisciplinary team